Isolation and characterization of fusidic acid-resistant, sporulation-defective mutants of Bacillus subtilis. - Kobayashi, H (1977)
Fusidic acid-resistant, sporulation-defective mutants were isolated from Bacillus subtilis 168 thy trp. About two-thirds of the fusidic acid-resistant (fusr) mutants were defective in sporulation ability and fell into three classes with respect to sporulation character. The representative mutants FUS426 and FUS429 were characterized in detail. FUS426 [fusr spo (Ts)], a temperature-sensitive sporulation mutant, grew well at 30 and 42 degrees C but did not sporulate at 42 degrees C. FUS429 [fusr spo (Con)], conditional sporulation mutant, grew and sporulated normally in the absence of fusidic acid, but its sporulation and growth rates decreased in the presence of fusidic acid, depending on the concentration of the drug. Although electron microscopic observation showed that both mutants were blocked at stage I of sporulation, the physiological analyses indicate that these mutants belong to the SpoOB class. Both mutants formed a thickened cell wall as compared with that of the parental strain. Genetic and in vitro protein synthesis analyses led to the conclusion that the sporulation-defective character of mutants FUS426 and FUS429 resulted from an alteration in elongation factor G caused by a single lesion in the fus locus. The possible role of elongation factor G in sporulation is discussed.